(untitled) (Eurasian Research Bulletin, 2022)
The number of emergency situations is increasing year by year. As a result of natural, man-made and environmental emergencies, about three thousand people die in our country every year, and more than ten thousand are injured in various degrees, and this figure is increasing. This shows the need to prevent and eliminate emergency situations. The following article describes the role of the database in preventing emergency situations and ways to improve it.